2020
DOI: 10.1152/japplphysiol.00205.2020
|View full text |Cite
|
Sign up to set email alerts
|

Inhalational delivery of induced pluripotent stem cell secretome improves postpneumonectomy lung structure and function

Abstract: Cell-free secretory products (secretome) of human induced pluripotent stem cells (iPSCs) have been shown to attenuate tissue injury and facilitate repair and recovery. To examine whether iPSC secretome facilitates mechanically-induced compensatory responses following unilateral pneumonectomy (PNX), litter-matched young adult female hounds underwent right PNX (removing 55-58% of lung units) followed by inhalational delivery of either the nebulized conditioned media containing iPSCs secretome (iPSC CM) or contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…For example, treatments with CM from human induced pluripotent stem cells (iPSCs) were delivered by inhalation every 5 days following unilateral pneumonectomy (PNX) in a dog model of destructive lung disease. This study revealed that repetitive inhalation of the iPSC secretome increased alveolar angiogenesis and enhanced septal remodeling associated with improved gas exchange compensation in the lungs (Dane et al, 2020). Moreover, intranasal delivery of the MSC secretome may also have neuroprotective effects, as shown in a study evaluating the efficacy of the secretome of the human amnion-derived multipotent progenitor cells, named ST266 (Grinblat et al, 2018).…”
Section: Delivery Of the Msc Secretomementioning
confidence: 89%
See 1 more Smart Citation
“…For example, treatments with CM from human induced pluripotent stem cells (iPSCs) were delivered by inhalation every 5 days following unilateral pneumonectomy (PNX) in a dog model of destructive lung disease. This study revealed that repetitive inhalation of the iPSC secretome increased alveolar angiogenesis and enhanced septal remodeling associated with improved gas exchange compensation in the lungs (Dane et al, 2020). Moreover, intranasal delivery of the MSC secretome may also have neuroprotective effects, as shown in a study evaluating the efficacy of the secretome of the human amnion-derived multipotent progenitor cells, named ST266 (Grinblat et al, 2018).…”
Section: Delivery Of the Msc Secretomementioning
confidence: 89%
“…Direct administration includes the injection or application of CM from cultured MSCs at the site of injury, e.g., cutaneous wounds, as well as the injection of exosomes (EXOs) systemically into the blood stream (Daneshmandi et al, 2020). The MSC secretome may also be delivered directly by inhalation for certain diseases (Khan et al, 2017;Grinblat et al, 2018;Dane et al, 2020). For example, treatments with CM from human induced pluripotent stem cells (iPSCs) were delivered by inhalation every 5 days following unilateral pneumonectomy (PNX) in a dog model of destructive lung disease.…”
Section: Delivery Of the Msc Secretomementioning
confidence: 99%
“…To date, only one study has been conducted in dogs, serving as canine model for using human iPSC-derived cell-free secretome to enhance post-pneumonectomy compensatory response. Human iPSC-derived secretome showed improved angiogenesis and alveolar remodeling leading to enhanced gas exchange after the pneumonectomy ( 191 ). This highlights the therapeutic potential of iPSC-derived secretome and EVs in human and veterinary patients, particularly due to their ease of administration.…”
Section: Applications Of Ipscs In Companion Animalsmentioning
confidence: 99%
“…HiPSCs are derived from adult somatic cells and are reprogrammed into a pluripotent state by induced expression of certain transcription factors, such as Oct4, Sox2, Myc and Klf4 [118,119]. Induced pluripotent stem cell (iPSC) secretome, including EVs has been reported to improve hyperoxia-induced acute lung injury, bleomycin-induced fibrosis, and postpneumonectomy lung structure and function [59,[120][121][122]. However, clear evidence for the efficacy of iPSC-derived EVs in improving lung diseases remain elusive, although one study may have shown some beneficial effects [59].…”
Section: Ev Therapy For Lung Regenerationmentioning
confidence: 99%